Effect of four levels of shade on survival, morphology and chlorophyll fluorescence of Nothofagus alessandrii container-grown seedlings - Santelices-Moya, Rómulo (2017)
Nothofagus alessandrii (ruil) is a threatened, endemic tree of the Mediterranean zone of Chile. As a result of past anthropogenic activities, its current cover has been reduced to only 314 hectares across several fragmented and degraded areas. Although activities to conserve and recover such forests have been developed, little is known about their propagation and nursery cultivation, since the plant’s quality is one of the most important factors for restoration and reforestation plans, re-vegetation, or forest enrichment. The success of restoration programs in these areas will require improvements in plant production, being important to test the shade effects on seedling survival and growth. This paper reports the results of testing for survival, morphological and chlorophyll fluorescence differences in N. alessandrii seedlings grown for approximately 32 weeks in unshaded conditions and under three different levels of shading (18%, 50%, and 80% shade). Morphological traits (stem height, root collar diameter, specific leaf area, shoot and root biomass, and quality indexes) and survival were measured. Chlorophyll fluorescence was also measured to analyze the shade tolerance of the species. Analysis showed significant differences for most traits as a consequence of the shade level. Seedlings exposed to 18% shade showed the highest total dry biomass, while those exposed to 80% shade showed the highest survival rate (92%). Chlorophyll fluorescence was high in the unshaded conditions and medium in the 18-50% shade. Morphological and chlorophyll fluorescence responses differed greatly among shade levels and corresponded with the degree of shade tolerance of the species.